Sustainable landscaping growing a greener home - Claudin, Craig; Mohl, Steve; Post, Robert; Shopware (Firm). (Hamilton, N.J. Shopware, 2010)
Shows how a green approach to landscaping can reduce the amount of energy needed to heat and cool a house, the proper management of rainwater and runoff, the value of native plants and the benefits of green roofs. Includes site vists with landscape architects and designers.
Landscaping for an energy efficient home (10 min.)-- Beyond the green lawn (10 min.) -- Small spaces, green spaces (5 min.)-- Becoming a green water manager (10 min.)-- Up on the (green) roofs (5 min.)
Editors, Steve Mohl, Craig Claudin.
Host, Robert Post.
DVD.
Keywords: Ecological landscape design; Sustainable architecture; Landscape design; Lawn ecology; Ground cover plants; Lawns -- Water requirements; Green roofs (Gardening); Water in landscape architecture; Video discs